Science Flipbook Integrated Al-Quran: Needs Analysis - Muhammad Aris Aris; Ariswan; Asri Widowati; Arina Zaida Ilma (Jurnal Penelitian Pendidikan IPA, 2023)
The current state of science learning in madrasah reveals a lack of integration between teaching materials and technology, as well as a failure to incorporate relevant al-Qur'an verses connecting propositions to scientific content. Moreover, the absence of assessments evaluating students' motivating attitudes toward learning further compounds these challenges. This study seeks to assess the necessity of developing integrated teaching materials for science education in Temanggung Regency's madrasah, employing flip books as a technological tool. Participants included six science teachers and nine students, and data was collected through interviews. Analysis involved data reduction, presentation, and conclusion. The findings indicate a shared need among teachers and students for teaching materials that seamlessly blend technology and al-Qur'an verses through flipbooks in science education. Consequently, future research should focus on the development of flipbooks that incorporate al-Qur'an verses as integral components of teaching materials for enhanced science learning experiences.